1987
DOI: 10.1007/bf00179925
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-calcium channel antagonist interactions

Abstract: Diltiazem, a benzothiazepine calcium channel antagonist, was given to six healthy men as a single 60 mg oral dose 120 min before IV injection of cocaine (0.2 mg/kg) in a double-blind, placebo-controlled, two-session study. Diltiazem alone produced no significant effects. Cocaine increased blood pressure, heart rate, pupil size and subjective "high" ratings, and decreased skin temperature. Diltiazem pretreatment diminished the cocaine effect on skin temperature, but did not otherwise alter the response to cocai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Single-dose bromocriptine efficacy has been demonstrated in a placebo-controlled, double-blind, laboratory evaluation (51), but out patient treatment trials of bromocriptine and a similar dopaminergic agent, amantadine, are limited, and similar methylphenidate reductions of crav ing were found to be transient when applied clinically (39). [Possible stimulant blockade has also been tried using calcium channel blockers (52), lithium (21), trazadone (49), imipramine, or neuroleptics (36), but these have not yet demonstrated clinically useful blockade of cocaine effects. ]…”
Section: Experimental Pharmacotherapiesmentioning
confidence: 99%
“…Single-dose bromocriptine efficacy has been demonstrated in a placebo-controlled, double-blind, laboratory evaluation (51), but out patient treatment trials of bromocriptine and a similar dopaminergic agent, amantadine, are limited, and similar methylphenidate reductions of crav ing were found to be transient when applied clinically (39). [Possible stimulant blockade has also been tried using calcium channel blockers (52), lithium (21), trazadone (49), imipramine, or neuroleptics (36), but these have not yet demonstrated clinically useful blockade of cocaine effects. ]…”
Section: Experimental Pharmacotherapiesmentioning
confidence: 99%
“…Heart rate induced effects on skin temperature, but not on cardiovascular or subjective effects (Rowbotham et al 1987). These latter results were possibly due to diltiazem's not crossing the blood-brain barrier.…”
mentioning
confidence: 97%
“…On this basis two groups have carried out double-blind studies comparing the effect of calcium channel antagonists with placebo on both the cardiovascular and psychological effects of intravenous cocaine in human volunteers who have previously used cocaine. One study, in six subjects, showed that diltiazem was ineffective at blocking either the cardiovascular or psychological effects of cocaine (Rowbotham et al, 1987), whilst another, in ten subjects, showed that, whilst nifedipine did not reduce the cardiovascular effects of cocaine, it did attenuate some of the psychological effects (Muntaner et al, 1991). This latter finding might perhaps be considered surprising, since the main biochemical action of cocaine is to increase dopamine neurotransmission and L-type channel antagonists probably do not inhibit basal dopamine release (Table 3).…”
Section: Cocaine Dependencementioning
confidence: 99%